Type 2 diabetes mediated heart failure: focus on early recognition and clinical strategies - Chen, Xi; Li, Wei; Zheng, Junwei; Huang, Meinv; Wang, Jinxi; Wu, Meifang (Frontiers in Endocrinology, 2025)
Type 2 diabetes mellitus (T2DM) is an important risk factor for the development of heart failure (HF), both directly by impairing cardiac function and indirectly through related conditions such as hypertension, coronary heart disease, renal dysfunction, and other metabolic disorders. The prevention of T2DM-related HF is a comprehensive management process involving complex and multifactorial pathogenic mechanisms. An in-depth exploration of the pathophysiological and clinical risk factors of HF in T2DM can assist clinicians in identifying individuals at high risk of HF, enabling early intervention measures to prevent its onset. In this review, we present data on the pathophysiology and epidemiology of T2DM-mediated HF, clinical phenotypic features of cardiomyopathy, and summarize clinical risk factors predicting HF development identified in multiple studies, risk assessment tools, and clinical trial data on the efficacy of lifestyle modifications, pharmacological treatments, and bariatric surgical interventions. Finally, we discuss best practice recommendations for clinicians, highlight potential limitations and challenges, and propose possible future research directions.